CD47‐ and Integrin α4/β1‐Comodified‐Macrophage‐Membrane‐Coated Nanoparticles Enable Delivery of Colchicine to Atherosclerotic Plaque. Issue 4 (27th November 2021) - Li, Yuyu; Che, Junyi; Chang, Lei; Guo, Meng; Bao, Xue; Mu, Dan; Sun, Xuan; Zhang, Xin; Lu, Wen; Xie, Jun
Abstract: Atherosclerosis is a chronic inflammatory disease and the major pathological factor of most cardiovascular diseases, leading to ≈1/3 of deaths worldwide. Improving local delivery of anti‐inflammatory drugs to the site of atherosclerosis has significant promise to prevent the development of atherosclerotic plaque clinically. Here, a modified‐macrophage‐membrane‐coated nanoparticle drug delivery able to transport colchicine to the atherosclerotic site is reported. This hybrid system efficiently targets endothelial cells under an inflammatory environment while escaping the endocytosis of macrophages. Furthermore, the anti‐inflammatory effect of the modified‐macrophage‐membrane‐coated nanoparticles on foam cells is studied. In vivo, the migration of the modified‐macrophage‐membrane‐coated nanoparticles to atherosclerotic lesions is confirmed in a vulnerable atherosclerotic plaque mouse model. Intravenous injections of the hybrid system successfully reduce the lipid plaque load and improve the plaque stability. This strategy provides a potential therapeutic system for the targeted delivery of anti‐inflammatory drugs to the atherosclerotic site for the treatment of atherosclerosis in cardiovascular diseases. Abstract : A modified‐macrophage‐membrane (MMM)‐coated nanoparticle drug delivery system able to transport colchicine to the atherosclerotic site is developed. The macrophage membrane is modified to highly express integrin α 4/ β 1 and clusters of differentiation 47 (CD47), which contributes to effective accumulation of the MMM‐coated colchicine‐encapsulated poly(lactic‐ co ‐glycolic acid) nanoparticles in atherosclerotic plaque and inhibition of the clearance by circulating phagocytotic cells.